Calculation of the Effective Stopping Power of Ions Generated by Neutrons in Tissue Constituents - Saion, Elias; Watt, D. E. (1992)
This paper reports the calculation of stopping powers of heavy charged particles generated by neutrons in four-element tissue constituents for particle energies from 0.1 keY to 1.0 MeV. At low projectile energies of less than 30 keV/amu where the nuclear stopping phenomenon is more dominant than the electronic stopping phenomenon, the effective stopping power values are higher than the continuous slowing-down approximation (CSDA) values, from which the deviation is dependent upon the target mass and the energy and mass of the projectiles.